2014
DOI: 10.1007/s11906-014-0476-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemoreflexes, Sleep Apnea, and Sympathetic Dysregulation

Abstract: Obstructive sleep apnea (OSA) and hypertension are closely linked conditions. Disordered breathing events in OSA are characterized by increasing efforts against an occluded airway whilst asleep, resulting in a marked sympathetic response. This is predominantly due to hypoxemia activating the chemoreflexes, resulting in reflex increases in sympathetic neural outflow. In addition, apnea, and the consequent lack of inhibition of the sympathetic system that occurs with lung inflation during normal breathing, poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 177 publications
(190 reference statements)
2
75
0
1
Order By: Relevance
“…21,22 Older subjects therefore are less likely to show effect of oxygen desaturation on blood pressure, if any. Second, as shown in the present study and numerous previous studies, 11,23,24 heart rate and sympathetic over-activation might be a pathogenic mechanism for hypertension associated with hypoxia and hypoxemia in obstructive sleep apnea. Both sympathetic nervous function and the heart rate response to sympathetic activation tend to be impairing with age advancing.…”
Section: Ambulatory Recording Modelsupporting
confidence: 82%
See 1 more Smart Citation
“…21,22 Older subjects therefore are less likely to show effect of oxygen desaturation on blood pressure, if any. Second, as shown in the present study and numerous previous studies, 11,23,24 heart rate and sympathetic over-activation might be a pathogenic mechanism for hypertension associated with hypoxia and hypoxemia in obstructive sleep apnea. Both sympathetic nervous function and the heart rate response to sympathetic activation tend to be impairing with age advancing.…”
Section: Ambulatory Recording Modelsupporting
confidence: 82%
“…ODI was assessed by overnight finger pulse oximetry in 2342 participants on the day of ambulatory BP monitoring, and calculated as the number of desaturation episodes per sleeping hour. Both BP and pulse rate increased significantly (P ≤ .006) from normal (< 5 events/h) to mildly (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), moderately (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and severely (≥ 30 events/h) elevated ODI. The association for BP was substantially attenuated by accounting for pulse rate (partial r² from .003-.012 to .002-.006).…”
Section: O R I G I N a L P A P E Rmentioning
confidence: 98%
“…However, the exact mechanism by which the vascular tonus has been increased, marked by high blood pressure, in subjects with OSA-induced intermittent hypoxia is not clearly understood. It has been suggested that the increased blood pressure on walking up might be related to disturbance of sympathetic and para-sympathetic nervous system with predominance of vasoconstriction [26,27]. The result of the present study revealed the NO 2 -concentration in peripheral blood in subjects with oxygen desaturation (SpO 2 <93%) was significantly lower than that in subjects without oxygen desaturation (Table 4).…”
Section: Discussionmentioning
confidence: 42%
“…Hypoxia and microarousals induce sympathetic activation, endothelial dysfunction, systemic inflammation, oxidative stress, and metabolic abnormalities, thereby increasing the risk for systemic blood and pulmonary hypertension, arrhythmia, myocardial infarction, congestive heart failure, and stroke [3,4,5,6,7]. Ophthalmological disorders are also reported in patients affected by OSA, including nonischemic anterior optic neuropathy, central serous retinopathy, floppy eyelid syndrome, primary open-angle glaucoma, normal-tension glaucoma, and papilledema [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%